Landslide Monitoring and Warning System Based on Wireless Sensor Network - Widodo, Ahmad Wahyu; Susanto, Misfa; Setyawan, FX Arinto (ELKHA : Jurnal Teknik Elektro, 2024)
Landslides are common in Indonesia, often caused by factors like heavy rainfall and high soil moisture levels. The Batubrak mini hydro power plant intake area in Lampung province of Indonesia has experienced landslides, prompting the need for an early warning system. This study presents the development of a cost-effective and efficient real-time landslide monitoring and warning system. The system incorporates sensors to measure accelerometer and vibration parameters, enabling real-time data display through a wireless sensor network and SCADA software. Early warnings are issued when triggers are activated. Three sensor nodes were deployed in the intake area for testing, demonstrating their ability to detect, collect, process, and transmit accelerometer and vibration data to the gateway node.